2000
DOI: 10.1103/physrevlett.84.4954
|View full text |Cite
|
Sign up to set email alerts
|

Interband Scattering and the “Metallic Phase” of Two-Dimensional Holes in GaAs/AlGaAs

Abstract: The "metallic" characteristics of high density holes in GaAs/AlGaAs heterostructures are attributed to inelastic scattering between the two split heavy hole bands. Landau fan diagrams and weak field magnetoresistance are employed to measure the interband scattering rate. The inelastic rate is found to depend on temperature with an activation energy similar to that characterizing the longitudinal resistance. It is argued that acoustic plasmon mediated Coulomb scattering might be responsible for the Arrhenius de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
50
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 25 publications
7
50
0
Order By: Relevance
“…ÿelds [145], inter-valley scattering [292], etc.-from the singular e ects due to impurities and interactions. The separation is at present a matter of some debate.…”
Section: Discussion Of the Experiments In Light Of The Theory Of Intementioning
confidence: 99%
“…ÿelds [145], inter-valley scattering [292], etc.-from the singular e ects due to impurities and interactions. The separation is at present a matter of some debate.…”
Section: Discussion Of the Experiments In Light Of The Theory Of Intementioning
confidence: 99%
“…The associated metal-toinsulator transition (MIT) has subsequently become the subject of intense interest and controversy [3]. While behavior similar to that of Ref.[2] has now been reported for a wide variety of 2D carrier systems such as n-AlAs, 10], and p-Si/SiGe [11,12], the origin of the metallic state and its transition into the insulating phase remain major puzzles in solid state physics.Several experiments have demonstrated the important role of the spin degree of freedom in the MIT problem, either in systems with a strong spin-orbit interaction [10,13,14], or via the application of an external magnetic field to spin polarize the carriers [15,16,17,18,19]. The latter experiments have shown that a magnetic field applied parallel to the 2DES plane suppresses the metallic temperature dependence, ultimately driving the 2DES into the insulating regime as the 2DES is spin polarized.…”
mentioning
confidence: 99%
“…Several experiments have demonstrated the important role of the spin degree of freedom in the MIT problem, either in systems with a strong spin-orbit interaction [10,13,14], or via the application of an external magnetic field to spin polarize the carriers [15,16,17,18,19]. The latter experiments have shown that a magnetic field applied parallel to the 2DES plane suppresses the metallic temperature dependence, ultimately driving the 2DES into the insulating regime as the 2DES is spin polarized.…”
mentioning
confidence: 99%
“…The hole density p in the 'metallic' region is varied by the gate voltage in the range (2.09 − 9.4) × 10 10 cm −2 , corresponding to the interaction parameter r s = 10 − 17 (with the effective mass m * taken as 0.38m e [9]). In [10,11] the 'metallic' character of a higher density 2DHG in GaAs was explained in terms of inelastic scattering between two hole subbands, split due to spin-orbit interaction. In our low-density structures the effect of the band splitting is negligible.…”
mentioning
confidence: 99%